Genotype score related to hepcidin regulation is associated with iron status in Japanese male athletes - Takaragawa, M.; Miyamoto-Mikami, E.; Nagato, S.; Nakamura, A.; Yamazaki, K.; Fuku, N. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Athletes are likely to be more susceptible to iron deficiency and anemia than the general population, due to the fact that they lose more iron as a result of hemolysis and sweating (Rodenberg et al., Corr Sports Med Rep, 2007). Athletes are therefore advised to increase their iron intake. However, factors involved in interindividual differences of intestinal iron absorption have received little attention in general instruction. Iron levels in the body are tightly regulated by hepcidin hormones, which alter the rate of intestinal iron absorption: high levels of hepcidin lead to lower iron absorption, while lower levels of hepcidin lead to higher iron absorption. Previous studies have reported that hepcidin levels are influenced by genetic factors. Therefore, this study examined the association between genetic factors involved in hepcidin regulation and iron status in athletes. METHODS: A total of 147 Japanese male collegiate track and field athletes were enrolled. These athletes were subjected to a fasting blood draw, a diet and iron supplements survey questionnaire, and saliva collection. Serum ferritin and iron levels were evaluated using latex agglutination turbidimetry and direct colorimetry methods, respectively. Serum hepcidin was measured in duplicate using the Hepcidin-25 ELISA kit according to the protocol provided by the manufacturer. Genetic polymorphisms associated with hepcidin regulation (TMPRSS6 rs855791 T/C, KDM3AP1-SLC40A1 rs12693541 C/T, KDM3AP1-SLC40A1 rs744653 C/T, TFR2 rs7385804, and HFE rs1799945) were analyzed using the TaqMan SNP Genotyping Assay. An individual`s genotype score was calculated as follows: a score of 0, 1, and 2 was assigned to each genetic polymorphism, starting with the allele predicted to have high hepcidin levels, from which the total score of the five genetic polymorphisms was calculated. RESULTS: In linear models, higher genotype scores exhibited a significantly lower hepcidin concentration normalized by ferritin concentration (R2 = 0.22, P = 0.030). In addition, the higher genotype scores indicated significantly higher serum iron and ferritin concentrations (R2 = 0.06, P = 0.003 and R2 = 0.06, P = 0.005, respectively). No significant correlation was observed between the genotype score and the iron or vitamin C intake. The daily iron intake of the athletes was 17.6 g/day, which was more than double the mean iron intake (7.4 g/day) of Japanese general males aged 20-29 years. However, the daily iron intake indicated a significant negative correlation with iron status (serum iron: r = *0.18, P = 0.03 and ferritin: r = *0.17, P = 0.04, respectively). CONCLUSION: Genetic factors involved in hepcidin regulation are associated with iron status in Japanese male collegiate athletes. Our results suggest that genetic information could be used to develop a novel dietary approach that considers iron absorption from the intestinal tract.